2015
DOI: 10.3343/alm.2015.35.4.445
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Modified Formalin-Ether Concentration Method Using Para Tube in Clinical Settings

Abstract: Conventional formalin-ether concentration method is a gold standard for the diagnosis of parasite infection. However, it may be time-consuming and laborious. We aimed to reveal the clinical usefulness of a modified formalin-ether concentration method using the Para Tube (KS Corporation, Korea) compared with the conventional method. A total of 117 fresh, unpreserved fecal samples composed to 90 negative controls and 27 positive controls with ova of Diphyllobothrium latum/D. nihonkaiense, ova of Clonorchis sinen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…This study used a standard protocol for the formalin ether concentration technique to detect parasite eggs [ 6 ]. Five grams of feces were dissolved in 15-20 mL of water.…”
Section: Methodsmentioning
confidence: 99%
“…This study used a standard protocol for the formalin ether concentration technique to detect parasite eggs [ 6 ]. Five grams of feces were dissolved in 15-20 mL of water.…”
Section: Methodsmentioning
confidence: 99%
“…PCR amplifications were performed using a CFX96 RT-PCR system (Bio-Rad) and a 20-μL reaction volume containing 10 μL of parasite reaction mixture, 5 μL of primer/probe mixture (each 500 nM of forward and reverse primers, 250 nM of probe) and 5 μL of DNA solution. The PCR proceeded as follows: pre-denaturing at 95°C for 10 min, 45 cycles of denaturation at 95°C with 15 sec, annealing and elongation at 60°C with 1 min [10]. Final identification was made to i) concordant results between two results obtained from multiplex PCR and conventional microscopy, and ii) sequencing result using individual primers when discordant results were obtained between the two methods.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, the formalin-ether diagnosed a high frequency of protozoan infections in general, and commensals in particular, as well as, a high sensitivity and negative predictive values in all group of protozoa infections. The conventional formalin-ether method is considered as a gold standard for the diagnosis of parasite infections (Won et al 2015). Some authors have considered this method as a valuable alternative to the Kato-Katz method for the diagnosis of soil-transmitted helminthes infections (Speich et al 2014); others showed the superiority of Ritchie's method over the direct wet mount for the diagnosis of protozoa infections in day care children (Mendoza et al 2003).…”
Section: Discussionmentioning
confidence: 99%